Membandingkan Efisiensi Pembiayaan Bank Umum Syariah dan Bank Umum Konvensional di Indonesia Dengan Metode Data Envelopment Analysis (DEA) - Sari, Ditta Feicyllia; Suprayogi, Noven (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This study aims to determine and comparing the level of financing efficiency of Islamic Banks and Conventional Bank in Indonesia. This study uses a quantitative non-parametric approach With Data Envelopment Analysis (DEA) VRS assumption, and a statistical tool Mann-Whitney U-Test. The samples are 10 Islamic Banks and 13 Conventional Commercial Bank those comply with the specified sample criteria. During 2010 to 2014, Islamic Bank has efficiency level of financing relatively higher than Conventional Bank based on VRS assumption. Source of inefficiency in Islamic Banks finance more due to inefficiency on ascale of financing . While the hypothesis test showed there are significant differences in the level of scale financing efficiency, and no significant difference in the level of financing efficiency between Islamic Banks and Conventional Banks in Indonesia with CRS and VRS assumption.